Assistive technology as a pillar of universal health coverage: qualitative analysis of stakeholder responses to the world health assembly resolution on assistive technology. (2nd October 2020) - Layton, Natasha; Bell, Diane; Borg, Johan; Steel, Emily; Maclachlan, Malcolm; Tebbutt, Emma; Khasnabis, Chapal; Swaminathan, Soumya
Abstract: Purpose: The importance of assistive technology (AT) as a pillar of universal health coverage was recognized at the 71st World Health Assembly (WHA) through the passing of Resolution 71.8 on improving access to AT (May 2018). A systematic analysis was conducted on the responses made to the Resolution by Member States and non-state actors, in order to provide a snapshot of global intent. Methods: Qualitative content analysis was conducted on over 40 written "Statements" made by Member States and non-state actors in response to Resolution 71.8. Results: The Resolution provides tangible guidance to the World Health Organisation (WHO) and its member states in order for them to meet commitments within the Convention on the Rights of Persons with Disabilities (CRPD). Statements made in response to the Resolution offer a unique plethora of multi-stakeholder views from differing global perspectives. Analysis identified a range of themes within two overarching themes: intersection of health, human rights and sustainable development; and international collaboration and support within an international agenda framework. Conclusion: The content analysis synthesises complex global data and identifies directions to positively influence national and regional AT policy and delivery. The complexity of factors demonstrates the importance of an AT systems-thinking approach; that is, the development and application of organised knowledge, skills, procedures and policies related to assistive products. AT systems thinking will be essential for AT to be effectively deployed as a pillar of universal health coverage. IMPLICATIONS FOR REHABILITATION: Assistive technology is a key facilitator of health and well-being, playing a critical role in global efforts to improve population health outcomes and strengthening health systems Access to assistive technology is a public health priority and is an essential health product to be covered under Universal Health Coverage Effective action on access to assistive technology must encompass the reality of diverse contexts yet common purposes expressed by global actors This analysis demonstrates the intersection of the health, human rights and sustainable development agendas, and the importance of international collaboration and support in achieving effective access